A fifth species of the genus Euparkerella (Griffths, 1959), the advertisement calls of E. robusta Izecksohn, 1988 and E. tridactyla Izecksohn, 1988, and a key for the Euparkerella species (Anura: Brachycephaloidea: Craugastoridae) - Hepp, Fábio; Carvalho-E-Silva, Sergio P. De; Carvalho-E-Silva, Ana M.p. Telles De; Folly, Manuella (Zootaxa, 2015)
A new species of the anuran genus Euparkerella is described from a rainforest area in the state of Rio de Janeiro, southeastern Brazil. Morphologically, the species resembles E. brasiliensis and E. cochranae, but differs from them in acoustic features. Relative to its congeners, the new species is characterized by: (1) medium size; (2) slender body; (3) narrow head; (4) long Finger IV, Toes I and V; (5) tubercles of the hand and foot protuberant; (6) duration of advertisement call longer than three seconds; (7) pulse-section rate slower than two sections/second; and (8) exhibiting pulse clusters. The advertisement calls of E. robusta and E. tridactyla are described and a key based on morphological and acoustic characters is presented for species in the genus.